Historiografi Hadis Hasan dan Dhaif - Syamsuez Salihima (Jurnal Adabiyah: Humanities and Islamic Studies, 2010)
Hadis is the second source of Islamic law beside al-Quran. It functions to explain the content of al-Quran. Some hadis we are reading/finding now is “text” regarded as Muhammad’s words. However, according to some result of hadis research, not all texts refered to Muhammad are considered hadis. Therefore there are many terms of Hadis we know so far such as shahih, hasan, daif and maudhu.  In some cases, there is not agreement among ulama to determine the originality of hadis. This disagreement is due to some criteria used in understanding hadis.